The right to education: progress, challenges and the road ahead - Shaheed, Farida (Frontiers in Education, 2026)
This essay is from the perspective of the mandate of the United Nations Special Rapporteur on the right to education, established to promote and protect universal access to education as a fundamental human right. Reflecting on 25 years of progress, it highlights that while there is global consensus on education as a driver of individual and societal well-being, there is less agreement on the content and purpose of education, and challenges of exclusion and discrimination. It reflects on some key issues relating to privatization, digitalization and education in crises, underscoring the risks they pose to equity and inclusivity. It emphasizes the need for robust governance and collaborative efforts to address these challenges while safeguarding education as a public and common good. The essay endorses calls for a reimagined vision of education, rooted in global solidarity and human rights that fosters critical thinking, creativity and social cohesion, addresses inequalities and prepares learners to navigate our complex changing world. It suggests that by prioritizing dignity, justice and equity, education can serve as a transformative force for sustainable inclusive futures. It urges strengthened international frameworks to protect education during crises, ensure inclusive policies and address emerging concerns like the ethical use of digital technologies and artificial intelligence.